PENGARUH PENGGUNAAN GAWAI TERHADAP PERKEMBANGAN SOSIAL EMOSIONAL ANAK DI TK DARMA WANITA 1 JEMBER - Kusumastutik, Nadila; Adi Putra, Wijaya; Kurniawan, Nurhafit (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to examine the influence of the use of devices on the social emotional development of children at Kindergarten Darma Wanita 1 Jember. The general aim of this research is to analyze the effect of using gadgets on the social emotional development of children at Kindergarten Darma Wanita 1 Jember. The research method used is quantitative research with this type of research ex post facto. And the data collection instrument uses a questionnaire/questionnaire with a Likert scale and documentation. The population in this study were 20 parents of children aged 5-6 years who attended TK Darma Wanita 1 Jember, and the sampling was determined based on a total sampling of 20 people. As well as analysis of this research data using the normality test, coefficient of determination, correlation coefficient, simple linear regression test, and t test. All these tests were carried out using SPSS 25 statistics. Based on the results of research conducted, there is an influence of the use of gadgets on the social emotional development of children at the Darma Wanita Kindergarten 1 Jember. This is proven by the results of the normality test using Kolmogorov Smirnov on SPSS 25.00, it is known that classes A and B, The significance value is 0.200 > 0.05, so it can be concluded that the residual value is normally distributed. And the results of the simple linear regression test show the results from class A, namely from the coefficients table, a significance value of 0.145 < 0.05 is obtained, and Class B, namely from the coefficients table, a significance value of 0.021 < 0.05 is obtained, so it can be concluded that variable variable Y. Furthermore, based on the class A correlation coefficient test, the pretest results are 0.145>0.05, as well as in the posttest table the significance value is 0.145>0.05. So it can be concluded that there is a correlation between the 2 variables, and the value of the Pearson correlation of the 2 variables is 0.527, which means the correlation relationship between the 2 variables is positive and is at a medium level. Meanwhile, class B shows the pretest results are 0.021>0.05, likewise in the posttest table the significance value is 0.021>0.05. So it can be concluded that there is a correlation between these 2 variables. The value of the Pearson correlation of the 2 variables is 0.680, which means the correlation relationship between the 2 variables is positive and is at a strong level. Furthermore, in the coefficient of determination test, it was found that the R Square value for class A was 0.278, so it could be concluded that the magnitude of the influence during the pre-test and after the post-test was 27.8%. Meanwhile, the R Square value for class B is 0.462, so it can be concluded that the magnitude of the influence during the pre-test and after the post-test was 46.2%. Lastly, the class A T test showed a result of 1.641 > 0.711, and class B showed a result of 2.781 > 0.703, so it can be concluded that variable X has an effect on variable Y. It is hoped that this research can provide practical guidance in managing the use of devices in early childhood, as well as help minimize the negative impact on their social emotional development.